(untitled) (Applied Biological Research, 2016)
The present study was conducted to assess the effect of vitamin-mineral supplemented diet and feeding strategies on reproductive performance of fish (Labeo rohita). Two diets, with and without vitamin-mineral mixture supplementation, were fed to Labeo rohita yearlings for a period of 8 months (April-November) at two feeding rates i.e. 3 and 4% b.w. and two feeding frequencies i.e. once and twice day-1. The study revealed that ganado-somatic index and relative fecundity were significantly higher in diet supplemented with vitamin-mineral mixture @ 4% b.w. fed twice a day during both pre-spawning (July) and post-spawning i.e. at resorption (September). Absolute fecundity and ova diameter were equally higher in control and treatment diets supplemented @ 4% b.w. twice day-1. The study suggests that supplementation of vitamin-mineral mixtureat higher feeding rate and frequency improves reproductive potential of Labeo rohita broodstock.